Creating the Future Workforce in Food, Agriculture, and Natural Resources: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The production of food and other agricultural goods is a fundamental human endeavor and a cornerstone of the U.S. economy. While careers related to agriculture and natural resources have evolved in response to new knowledge and technology, consumer demands, and environmental changes, these professional fields now face a critical challenge: the ability to recruit and maintain a robust workforce. Companies, government bodies, and research organizations involved in food, agriculture, and natural resources (areas referred to collectively as FANR) are struggling to attract the next generation of workers. This shortage is apparent in employment projections for both trade positions attainable with certificate programs and high-tech positions requiring advanced degrees. Factors such as an increasingly diverse population, shifting work and career views, and lucrative job opportunities in other fields impact the ability to recruit talented individuals into the agricultural workforce. To provide a forum for discussing how the community might come together to address this challenge, the National Academies of Sciences, Engineering, and Medicine held a workshop on February 10-11, 2016, in Washington, DC. There were approximately 100 participants from land-grant universities, non-land-grant universities, minority-serving universities, community colleges, high schools, professional societies, government bodies, and corporations - reflecting the wide diversity of organizations with a stake in the future FANR workforce. The workshop was designed not only to highlight the significance of the challenges but also to surface concrete, forward-looking opportunities for action. This Proceedings of a Workshop summarizes plenary presentations from the workshop along with insights from 10 working groups that described key challenges, ongoing efforts to address them, and promising approaches for future action.
Keywords: Agriculture; Industry and Labor

Respiratory Diseases Research at NIOSH: Reviews of Research Programs of the National Institute for Occupational Safety and Health - National Research Council; Institute of Medicine (The National Academies Press, 2008)
Respiratory diseases caused by exposures to dangerous materials in the workplace have tremendous implications for worker health and, by extension, the national economy. The National Institute for Occupational Safety and Health (NIOSH) estimates that deaths from work-related respiratory diseases and cancers account for about 70% of all occupational disease deaths. NIOSH conducts research in order to detect and reduce work-related hazardous exposures, injuries, and diseases; its Respiratory Disease Research Program (RDRP) focuses on respiratory diseases. This National Research Council book reviews the RDRP to evaluate the 1) relevance of its work to improvements in occupational safety and health and 2) the impact of research in reducing workplace respiratory illnesses. The assessment reveals that the program has made essential contributions to preventing occupational respiratory disease. The National Research Council has rated the Program a 5 out of 5 for relevance, and a 4 out of 5 for impact. To further increase its effectiveness, the Respiratory Disease Research Program should continue and expand its current efforts, provide resources for occupational disease surveillance, and include exposure assessment scientists in its activities.
Keywords: Health and Medicine; Industry and Labor

Minorities in the Chemical Workforce: Diversity Models that Work: A Workshop Report to the Chemical Sciences Roundtable - National Research Council (The National Academies Press, 2003)
This report to the Chemical Sciences Roundtable presents a collection of contributed papers that report success stories for increasing diversity. The report provides background information on the value of diversity in the undergraduate environment, and the success stories address both undergraduate and graduate chemistry programs as well as chemical industry.
Keywords: Industry and Labor; Education

Safety is Seguridad: A Workshop Summary - National Research Council (The National Academies Press, 2003)
Approximately 32.8 million persons of Hispanic descent live in the United States, half of whom were born outside the United States (Therrien and Ramirez, 2000). By the year 2050, it is expected that Hispanics will constitute more than 25 percent of the total U.S. population and approximately 15 percent of the U.S. labor force. These estimates and the fact that 90 percent of Hispanic American men and 60 percent of Hispanic American women participate in the U.S. workforce strongly suggest a need for occupational safety and health information in Spanish.
Keywords: Industry and Labor; Earth Sciences

Trends in the Early Careers of Life Scientists - National Research Council (The National Academies Press, 1998)
In each year between 1994 and 1996, more than 7,000 individuals received a Ph.D. in life-science, and the number of graduates is rising sharply. If present trends continue, about half of those graduates will have found permanent positions as independent researchers within ten years after graduation. These statistics—and the labor market situation they reflect—can be viewed either positively or negatively depending on whether one is a young scientist seeking a career or an established investigator whose productivity depends on the labor provided by an abundant number of graduate students. This book examines the data concerning the production of doctorates in life-science and the changes in the kinds of positions graduates have obtained. It discusses the impact of those changes and suggests ways to deal with the challenges of supply versus demand for life-science Ph.D. graduates. Trends in the Early Careers of Life Scientists will serve as an information resource for young scientists deciding on career paths and as a basis for discussion by educators and policymakers as they examine the current system of education linked to research and decide if changes in that system are needed.
Keywords: Policy for Science and Technology; Industry and Labor

Preparing Chemists and Chemical Engineers for a Globally Oriented Workforce: A Workshop Report to the Chemical Sciences Roundtable - National Research Council (The National Academies Press, 2004)
Globalization—the flow of people, goods, services, capital, and technology across international borders—is significantly impacting the chemistry and chemical engineering professions. Chemical companies are seeking new ideas, a trained workforce, and new market opportunities regardless of geographic location. During an October 2003 workshop, leaders in chemistry and chemical engineering from industry, academia, government, and private funding organizations explored the implications of an increasingly global research environment for the chemistry and chemical engineering workforce. The workshop presentations described deficiencies in the current educational system and the need to create and sustain a globally aware workforce in the near future. The goal of the workshop was to inform the Chemical Sciences Roundtable, which provides a science-oriented, apolitical forum for leaders in the chemical sciences to discuss chemically related issues affecting government, industry, and universities.
Keywords: Industry and Labor; Math, Chemistry, and Physics

Measuring Respirator Use in the Workplace - National Research Council (The National Academies Press, 2007)
Respirators are used in a variety of workplaces including emergency response, mining operations, construction, manufacturing, and hospitals. In 2001, National Institute of Occupational Safety and Health (NIOSH) and Bureau of Labor Statistics commissioned a nationwide survey of respirator use in the workplace, the results of which were published in the 2003 report Respirator Usage in Private Sector Firms. The purpose of the survey was to evaluate respirator use and practices, including training practices and the value of respirator manufacturer's instruction, in order to help guide NIOSH respirator certification and research. This National Research Council (NRC) report evaluates the survey in terms of several measures such as the adequacy and appropriateness of the survey instrument, the survey methodology, data analysis, and the conclusions drawn from the data. The NRC report finds that the survey was an important first step in collecting respiratory protection data from a probability sample but that several improvements could be made in survey design and analysis. Based on the review of the survey, the NRC report concludes that data on respirator use would be best provided by employers and employees in the context of the work setting.
Keywords: Industry and Labor; Health and Medicine

Understanding Interventions That Encourage Minorities to Pursue Research Careers: Summary of a Workshop - National Research Council (The National Academies Press, 2007)
Minority groups are severely underrepresented in the scientific workforce. To encourage minorities to pursue careers in research, a variety of "intervention programs" have been created at the pre-college, college, and graduate school levels. While there is a belief that these programs often achieve their goals, there is relatively little understanding of the factors that contribute to that success. The Division of Minority Opportunities in Research (MORE) at the National Institute of General Medical Sciences of the National Institutes of Health has established a grant program to support research to better understand the factors that contribute to the success of intervention programs. The MORE Division asked the National Academies to organize a workshop focusing on issues addressed by the grant program. This workshop summary presents examples of previous research on intervention programs, describes ways to formulate effective research questions and conduct research to identify the key elements that lead to successful intervention programs, and outlines ways to foster a community of researchers in this area.
Keywords: Education; Policy for Science and Technology; Engineering and Technology; Industry and Labor

A Smarter National Surveillance System for Occupational Safety and Health in the 21st Century - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The workplace is where 156 million working adults in the United States spend many waking hours, and it has a profound influence on health and well-being. Although some occupations and work-related activities are more hazardous than others and face higher rates of injuries, illness, disease, and fatalities, workers in all occupations face some form of work-related safety and health concerns. Understanding those risks to prevent injury, illness, or even fatal incidents is an important function of society.
Keywords: Health and Medicine; Behavioral and Social Sciences; Industry and Labor; Surveys and Statistics